2014
DOI: 10.1371/journal.pone.0099444
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Attenuates Splenocyte-Induced Demyelination in Cerebellar Slice Cultures

Abstract: The family of sphingosine-1-phosphate receptors (S1PRs) is G-protein-coupled, comprised of subtypes S1PR1-S1PR5 and activated by the endogenous ligand S1P. The phosphorylated version of Fingolimod (pFTY720), an oral therapy for multiple sclerosis (MS), induces S1PR1 internalisation in T cells, subsequent insensitivity to S1P gradients and sequestering of these cells within lymphoid organs, thus limiting immune response. S1PRs are also expressed in neuronal and glial cells where pFTY720 is suggested to directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…5A). In agreement with our previous studies (Pritchard et al, 2014;Sheridan and Dev, 2012), pFTY720 attenuated LPC-induced demyelination compared with control, as observed by expression of myelin oligodendrocyte glycoprotein (MOG) (Fig. 5B) and myelin basic protein (MBP) (Fig.…”
Section: Psychosine Potentiates Lipopolysaccharide (Lps)-induced Levesupporting
confidence: 92%
See 3 more Smart Citations
“…5A). In agreement with our previous studies (Pritchard et al, 2014;Sheridan and Dev, 2012), pFTY720 attenuated LPC-induced demyelination compared with control, as observed by expression of myelin oligodendrocyte glycoprotein (MOG) (Fig. 5B) and myelin basic protein (MBP) (Fig.…”
Section: Psychosine Potentiates Lipopolysaccharide (Lps)-induced Levesupporting
confidence: 92%
“…Specific treatment details are indicated in the figure legends. Organotypic cerebellar slice cultures were prepared exactly as we have described previously (Pritchard et al, 2014;Sheridan and Dev, 2012). In brief, tissue isolated from postnatal day 10 (P10) C57BL/6 mice and 400 µm parasagittal slices of cerebellum were grown on cell culture inserts (5-6 slices each) (Millicell PICMORG50 Millipore).…”
Section: Astrocyte and Cerebellar Slice Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…28,[46][47][48] Furthermore, it has also been shown that FTY720 can enhance remyelination in organotypic slice cultures. 27,49,50 In vivo studies demonstrated that FTY720 is effective at treating acute EAE by promoting OPC proliferation and differentiation and by stimulating the sonic hedgehog (Shh) signaling pathway. 51 These results, together with our findings, indicate that FTY720 has both anti-inflammatory and neuroregenerative effects.…”
Section: Discussionmentioning
confidence: 99%